An update on natural bioactive components of traditional preparations for the treatment of nephrolithiasis; a review - Pradeep Singh; Mohammad Sabir Alam; Muhammad Arif; Shazia Usmani; Mohammad Meraj Anjum; Vijay Bhalla; Arun Garg (Journal of Nephropharmacology, 2024)
Nephrolithiasis is a condition characterized by the formation of crystal concretions within the kidneys or urinary tract. This urological disorder is on the rise globally, affecting both male and female populations. Unfortunately, conventional medicines used in the treatment of nephrolithiasis often lead to certain complications, eventually resulting in end-stage renal disease. As a result, there has been a growing interest in seeking risk-free therapies from nature to address this issue caused by the undesired effects of synthetic drugs. Evidence-based traditional medicine has emerged as a significant approach to treating nephrolithiasis, gaining recognition within the scientific community. In this review, we summarize recent scientific reports on various herbal drugs with clinical relevance in the treatment of nephrolithiasis, utilizing them as part of traditional medicine practices in the Asian continent. Additionally, several traditional medicine formulations from Ayurveda, Unani, and homeopathic systems, known for their potential lithotriptic effects and clinical applications, are highlighted. The primary focus of this review is to explore the mechanisms involved in the formation of kidney stones and provide a concise compilation of therapeutically effective herbs used in nephrolithiasis treatment.